(3Odjd af NOeI GdYedGA hegGQGJ GdHjY (B/s - (3GHh HcQ, eUWai eMehOs; (3eQSj, LeGd GdOjf eMeOs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s)
(3eGgh GdLOjO aj JfXje hGOGQI fTGW GdJShjb hGdHjY ddJYGed eY HjFI GdGYeGd GdeYGUQI ? , eGgj JCKjQGJ CYeGd GdTQcI hXQhagG hHjFJgG Ydi GdSjGSGJ hNWW GdJShjb hGdHjY ? , cja fUee HfGA JfXej hfXGe GOGQj caA haYGd dfTGW GdJShjb hGdHjY ?, cja jchf dOjc LgGR HjY eMJQa jMbb GdHjY hGdJMUjd GdeNWW , eGgj GdGOhGJ GdGSGSjI dJNWjW hJfajP HjFI GdGYeGd GdHjY heJGHYJgG heJGHYJgG hJbjjegG ?, cja JacQ GSJQGJLjG hJVY GSJQGJLjI dGYeGd GdJShjb hGdHjYs
Keywords: (3GOGQI GdeHjYGJs; (3GdHjYs; (3GdJShjbs